(untitled) - Deamer, David W. (Boston, 1993)
This book may be used as a supplement to courses in cell biology, chemistry, evolution, system theory, and history and physiology of science, or as a primary text for a course on the orgins of life.
Keywords: Biochemistry,Life ( biology )